High Contrast Imaging of an Exoplanet with the Magellan VisAO Camera. Issue Volume 8:Issue S299(2013) (6th January 2014) - Males, Jared R.; Close, Laird M.; Morzinski, Katie M.; Kopon, Derek; Puglisi, Alfio; Gasho, Victor; Follette, Kate; Esposito, Simone; Riccardi, Armando; Pinna, Enrico; Xompero, Marco; Briguglio, Runa; et al.
Abstract: The Magellan Adaptive Optics (MagAO) system saw first light in November 2012 at Las Campanas Observatory (LCO) on the 6.5m Clay telescope. Here we present an introduction to MagAO's visible wavelength diffraction limited imager, VisAO. VisAO delivers Strehl ratios greater than 30% from 0.62 microns (r') through 1 micron, where Strehl is even higher, and achieved resolutions as small as 20 milli-arcseconds. We took advantage of the excellent performance of MagAO/VisAO to conduct high contrast observations of an exoplanet in the optical. With VisAO, we are, for the first time, able to begin characterizing exoplanet atmospheres in the optical from the ground.